Identification of novel genetic biomarkers for ChAdOx1 nCoV-19 mediated immunogenicity - Chou, Wan-Hsuan; Chang, Che-Mai; Ting, Jafit; Lin, Min-Rou; Liao, Hsin-Ni; Chou, Yi-Chien; Wei, Chun-Yu; Chi, Hsin-Hui; Ho, Szu-Ying; Luo, Wei-Tzu; Tsai, Cheng-Lin; Chao, Ching-Hsuan; et al. (Frontiers in Immunology, 2025)
BackgroundResearch comprehensively examining factors for COVID-19 DNA vaccine responses is lacking, particularly in Asian populations. This study aims to investigate biomarkers of reactogenic and immunogenic responses after DNA-based COVID-19 vaccination in a Taiwanese population.MethodsA genome-wide association study (GWAS) of 415 Taiwanese healthcare workers was conducted to identify genetic variants associated with reactogenic and immunogenic responses to the first and second doses of ChAdOx1 nCoV-19 vaccine. Furthermore, gene set enrichment analysis was conducted to elucidate the underlying biological pathways. Finally, a polygenic score (PGS) was utilized to assess the synergistic host effects on neutralizing antibody (NT50).ResultsWe identified 501 suggestive significant genetic associations with vaccine responses, enriched in lipid and lipophilic vitamin metabolism, interleukin signaling, and neurotransmitter release pathways. Moreover, we observed a combined effect of genetics with age and sex on NT50 after the second dose. Notably, the negative correlation between age and NT50 was stronger in lower PGS groups (ρlowPGS = -0.5, ρmediumPGS = -0.2, ρhighPGS = -0.0072).ConclusionOur study fills a critical gap by addressing the lack of research on genetic factors of ChAdOx1 nCoV-19 vaccine responses in Asian population, providing valuable insights into the genetic basis of DNA-based vaccine responses. The synergic host effect highlights the value of integrating genetic information with other host factors as a biomarker to predict individual vaccine responses. Our findings can contribute to personalized vaccination strategies and future vaccination policies.